Empty Fruit Bunches Compost and Germination of Raphanus sativs L. - Wahi, Rafeah; Yusup, Izzatul ’Adilah (Borneo Journal of Resource Science and Technology, 2016)
Overabundance of empty fruit bunches (EFB) from palm oil industries has opened opportunity for its exploitation for agricultural use as compost. In this study, palm oil EFB compost was prepared by the addition of wood chips as a bulking agent and chicken manure to enhance the composting rate. Moisture was maintained at 50-70% during the 2-month composting. Results showed that the EFB compost containing high mineralisation index compared to the initial EFB samples after two months of the composting process. The important macronutrients; N, P, K, Ca and Mg and micronutrients Fe, Zn, Mn, Ni, Cu and B were found present in the EFB composts. The final stage of EFB compost B showed high nutrient content with N, P, and K values of 2.21%, 3.65%, and 0.49%, respectively. Fe was the most outstanding element in the EFB compost as high as 9000 ppm. Germination results showed that EFB compost with EFB:wood chips at 1:3 ratio exhibited better growth of leaves and root of Raphanus sativs L. compared to 1:2 ratio. This indicated that the EFB compost is capable in improving soil fertility and growth of plants.